(untitled) (American & British Studies Annual, 2008)
This paper focuses on arguably the best contemporary British chronicler of historical and literary London, Peter Ackroyd. As its theoretical point of departure it deals with his seminal work on the city’s intertextual and discursive nature over the course of its development, London: The Biography (2000). In order to illustrate Ackroyd’s fictional historiographic treatment of different historical periods of London, two of his novels have been chosen – Hawksmoor (1985) and Dan Leno and the Limehouse Golem (1994), while three others, Chatterton (1987), The Clerkenwell Tales (2003) and The Lambs of London (2004), are also referred to. All these texts are discussed from the point of view of textual and thematic interconnectedness, the mixing of the factual and fictitious in creating London’s topography, and the influences of the city’s milieu on the characters’ psyches.